Pendampingan Pembuatan Laporan Keuangan UMKM Untuk Peningkatan Akses Modal Usaha - Harry Budiantoro; Perdana Wahyu Santosa; Hesti Juni Tambuati Subing; Nazma Riska Zhafiraah; Hestin Agus Tantri Ningsih (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
MSME is an abbreviation for Micro, Small and Medium Enterprises. Basically, MSMEs mean businesses or businesses carried out by individuals, groups, small business entities, or households. Indonesia as a developing country makes MSMEs the main foundation of the community's economic sector, this is done to encourage the ability of independence to develop in society, especially in the economic sector. Therefore, competent Human Resources (HR) are needed to produce quality financial reports. This activity is carried out through outreach, training and assistance to MSME actors in Mandalamekar Village. Based on the PKM activities that have been carried out, there are participants who are able to understand 87% of the material. Apart from that, based on the practice of making Financial Reports and how to make Financial Reports and producing four financial reports, they were successfully arranged neatly according to wishes and were able to be presented using a laptop, not manually as before. Significant managerial implications, especially in terms of increasing access to business capital. The following are several managerial implications that can be identified: the mentoring process will help MSME owners and managerial staff to increase their understanding of financial management.